2019
DOI: 10.4148/2161-4148.1043
|View full text |Cite
|
Sign up to set email alerts
|

Too Hard to Find with Too Little Time: What School Social Workers Want in Online Resources for Evidence-Based Practice

Abstract: School mental health practitioners, including social workers, are mandated through federal, state, and professional entities to provide evidence-based practices to students. Nevertheless, rates of use of evidence-based practices among mental health professionals in schools remain low, even as knowledge about effective practices increases. This study aimed to further knowledge about how to promote and support the use of evidence-based practices among school practitioners using online technology. School social w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent research on SSWs practice choices has shown that SSWs with less than 10 years' experience and working in states that require an MSW and some state certification are more likely to endorse the primary prevention work embedded in MTSS, and the ecologically informed practice work that involves providing direct support and services to families and communities (Shaffer & Fisher, 2017;Thompson et al, 2019). Other studies have shown that SSWs are eager to find ways to adapt their practice to their schools' evolving expectations while preserving what they perceive as their central clinical role (Phillippo et al, 2017;Webber, 2018), providing school-wide prevention services (Peckover et al, 2013), and finding ways to stay up-to-date with the best available evidence (Patak-Pietrafesa et al, 2019;Thompson & Frey, 2020).…”
Section: School Social Work Practice Before Covid-19mentioning
confidence: 99%
“…Recent research on SSWs practice choices has shown that SSWs with less than 10 years' experience and working in states that require an MSW and some state certification are more likely to endorse the primary prevention work embedded in MTSS, and the ecologically informed practice work that involves providing direct support and services to families and communities (Shaffer & Fisher, 2017;Thompson et al, 2019). Other studies have shown that SSWs are eager to find ways to adapt their practice to their schools' evolving expectations while preserving what they perceive as their central clinical role (Phillippo et al, 2017;Webber, 2018), providing school-wide prevention services (Peckover et al, 2013), and finding ways to stay up-to-date with the best available evidence (Patak-Pietrafesa et al, 2019;Thompson & Frey, 2020).…”
Section: School Social Work Practice Before Covid-19mentioning
confidence: 99%